Recommendations for rheumatology ultrasound training and practice in the UK. (7th November 2020) - Atchia, Ismaël; Brown, Andrew K; Chitale, Sarang; Ciechomska, Anna; Estrach, Cristina; Karim, Zunaid; Wakefield, Richard J
Abstract: Objective: The aim of this paper is to present a UK-based consensus of principles and recommendations to guide rheumatology US training and practice. Method: A Delphi process was conducted involving 19 US experts representing each of the 14 regions of the UK. A working group of experienced British Society for Rheumatology Ultrasound Special Interest Group (BSRUSSIG) members made seven proposals that were presented to the whole group for further discussion. This resulted in minor modifications and seven preliminary recommendations. Members were then asked to anonymously agree or disagree with each recommendation using an electronic ballot. A threshold of 75% was used to determine consensus agreement. Results were collated by an independent chairperson and presented to the BSRUSSIG in a face to face meeting where agreement for each recommendation was ratified and an action plan agreed for dissemination of the results and future development work. Results: Using a validated process, experts in rheumatology US have worked through an iterative process and have unanimously agreed seven recommendations for rheumatology training and practice. These cover a hierarchy of practice indications, education and training, including the need for practitioners to demonstrate lifelong learning, as well as a commitment to support mentors and trainers through the BSRUSSIG. Conclusion: These are the first specific education and practice recommendations for rheumatology US in the UK and have been developed and endorsed by the BSRUSSIG. We intend that these proposals will help to support and validate rheumatology US practice and inform the development of future rheumatology training curricula and education programmes.